Investigation of the impact of dual inoculations of arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria on drought tolerance of maize grown in a compost-amended field under Mediterranean conditions - Ouhaddou, Redouane; Ech-chatir, Lahoucine; Ikan, Chayma; Soussani, Fatima Ezzahra; Errouh, Farid; Boutasknit, Abderrahim; Rodrigez, Julio Cesar; Er-Raki, Salah; Duponnois, Robin; Meddich, Abdelilah (Frontiers in Microbiology, 2024)
Mis en forme : Police :12 pt Mis en forme : Anglais (États-Unis) In the current context of rapid climate change, water scarcity and soil poverty are becoming increasingly alarming, leading to growing losses of 30-50% of global agricultural production. It is imperative to find environmentally-friendly approaches for improving plant tolerance to drastic conditions, particularly in arid and semi-arid Mediterranean regions. Biostimulants based on symbiotic microbes are emerging as effective strategies for improving tolerance and agricultural productivity. This study aims to evaluate investigated the effects of single and double inoculation of arbuscular mycorrhizal fungi (My) and plant growth-promoting bacteria (Ba) on the growth, physiological and biochemical traits of maize crop grown in compost (Co) amended soil under two irrigation regimes: well-watered (WW: 100% of crop evapotranspiration (ETc)) and drought-stressed (DS: 50% ETc) using drip irrigation system. Reducing irrigation to 50% reduced shoot dry weight (SDW), root dry weight (RDW), 1000-grainsseed weight (TGW) and grain yield (Y). However, Ba alone increased SDW by 63%, while CoMyBa improved RDW, TGW and Y by 197%, 43% and 97175%, respectively compared with the control under DS conditions. Dual inoculation boosted root colonization intensity in maize seedlings grown in compost-amended soils., The dual inoculation positively affected the nNormalized dDifference vVegetation Iindex (NDVI), total chlorophyll and leaf area of maize seedlings in compost-amended soil, compared with to the controls. The single application of Ba significantly reduced hydrogen peroxide and malondialdehyde by 46%, in maize seedlings grown in compost-amended soil, compared to the controls under DS. Our results indicated that My and Ba significantly boost the ability of maize to tolerate drought by improving water supply and physiology and stimulating the accumulation of organic and inorganic osmolytes, as well as improving the properties of soils such as cation exchange capacity particularly amended by Co. The dual inoculations were proved to be the most effective and represent an environmentally-friendly and relatively inexpensive approach to optimizing agricultural production and soil restoration programs in Mediterranean regions.